Risk Factors and Clinical Course of Patients with Acute Kidney Injury: A Systematic Literature Review - Intan Nurcahyani; Septanti, Risti; Maya Arfania (HM Publisher, 2023)
Acute kidney injury (AKI) is a serious health problem and can be life-threatening if not treated quickly and appropriately. There are several risk factors that can increase a person's chances of experiencing AKI. This study aimed to carry out a systematic review to explore the risk factors for acute kidney injury and the clinical course of acute kidney injury. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding risk factors and clinical overview of acute kidney injury. The search was performed using the terms: (1)